2023
DOI: 10.1111/sjop.12895
|View full text |Cite
|
Sign up to set email alerts
|

WPPSI‐IV and NEPSY‐II performance in mono‐ and bilingual 5–6‐year‐old children: Findings from The FinSwed Study

Abstract: Children's language background relates to their neurocognitive development. Knowledge of this relationship is important as bilingualism is common. However, research regarding language background in relation to performance on cognitive tests such as the WPPSI‐IV and NEPSY‐II is scarce. The present study compared WPPSI‐IV and NEPSY‐II performances between 5‐ and 6‐year‐old Swedish‐speaking monolingual (n = 45) and Swedish‐Finnish‐speaking simultaneous bilingual (n = 34) children in Finland. The participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
(154 reference statements)
2
5
0
Order By: Relevance
“…This is quite surprising since there were no differences between mono- and bilingual Finland-Swedish children in nonverbal subtests of the WPPSI-R (Korkman et al, 2012). Korpinen et al (2023, based on the same data as the present study) have further discussed this result and the possibility of it being a chance finding. There was also a significant relationship between sex and the PSI, with girls scoring significantly higher.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is quite surprising since there were no differences between mono- and bilingual Finland-Swedish children in nonverbal subtests of the WPPSI-R (Korkman et al, 2012). Korpinen et al (2023, based on the same data as the present study) have further discussed this result and the possibility of it being a chance finding. There was also a significant relationship between sex and the PSI, with girls scoring significantly higher.…”
Section: Discussionsupporting
confidence: 80%
“…A similar trend was also found for the VCI, which measures verbal reasoning, verbal concept formulation, and acquired knowledge (Wechsler, 2012). Previously, the bilinguals in this study have been shown to perform significantly lower on Similarities, Vocabulary, and Picture Naming than monolinguals (Korpinen et al, 2023). Similar bilingual disadvantages in expressive vocabulary tasks have also been found previously in young Finland-Swedish children (Korkman et al, 2012;Westman et al, 2008) and internationally (e.g., Thordardottir, 2011).…”
Section: Differences In Verbal Subtests and Indexessupporting
confidence: 87%
See 2 more Smart Citations
“…Photographs of the facial features of 13 children were also collected as part of the study. To assess the children's developmental progress and cognitive abilities, two specific tools were used: Griffiths Development Scales-Chinese (GDS-C) [ 30 ] and Wechsler Preschool and Primary Scale of Intelligence–Fourth Edition (WPPSI-IV) [ 31 ]. GDS-C is a comprehensive tool for assessing the developmental progress of children from birth to 8 years across various areas, including gross and fine motor skills, personal/social abilities, language, and performance.…”
Section: Methodsmentioning
confidence: 99%